(untitled) (قضايا سياسية, 2022)
This research discussed the most prominent political effects of the recent normalization agreements (UAE. Bahrain, Morocco, Sudan) with "Israel", on the Palestinian issue internally and externally, on the external level, it leads to the disruption of principles established decades ago, and striking the roots of the centrality of the Palestinian issue in Arab communities, giving Israel the right to exist as a fait accompli or as a natural entity in the Arab region, and this serves the benefit of the colonial project, it contradicts the principle of “Palestine is the issue of land and humans”, and it contributes to finding channels for the Zionist media to infiltrate and try to broadcast its narrative and distort the Palestinian historical narrative, it works to strike the idea of the right to resistance and liberation. And it retroactively affects the various directions to solve the Palestinian issue, including adhering to historical Palestine (from the sea to the river), following the approach of armed confrontation adopted by the Palestinian resistance factions, and it affects the Palestinian Authority project (the two-state solution), which aims to establish a Palestinian state on the 1967 occupied area, and on the tools of resistance and confrontation, such as BDS movement, also it contributes to serving the settler-colonial project of the Palestinian land, and it leads to an increase in the occupation’s persistence in stealing Palestinian resources, Murder, arrest, and abuse, In addition, the escalation of violations against the holy Islamic and Christian places, especially the Al-Aqsa Mosque, which "Israel" aimed to move forward with its project of temporal and spatial division, and the Judaization of Jerusalem.